KEPADATAN POPULASI KODOK FEJERVARYA CANCRIVORA DI PERSAWAHAN KABUPATEN KARAWANG, JAWA BARAT - Kurniati, Hellen; Sulistyadi, Eko (JURNAL BIOLOGI INDONESIA, 2017)
ABSTRACTKarawang District is the largest producer of frog meat in West Java. To find out how the frog harvesting impacts to the represent condition of population in the wild, on 16-27 May 2016 population survey was conducted on paddy field in East Karawang by implementing transect method with total length was 3000 meters. The results of this transect method showed that the population of juvenile was the highest in most areas of transects, followed by pre-adult population. The population of adult individuals was at the lowest and most adult male individuals were detected by the call that they make. Conditions of water supply in rice fields also determine the conditions of juvenile and pre-adult populations; newly planted rice fields with high water availability obtained the highest population per unit area compared to the condition of paddy fields with a little water availability; but exceptions to the plowed rice fields, despite the availability of a lot of water but disturbance from human activities was also high. Average density per unit area m2 for a little watery rice fields to dry with a total length of 1500 meters transect were as follows: (1) juvenil density was 0.33 individuals/m2, (2) pre-adult density was 0.04 individuals/m2, (3) adult density was 0.005 individuals/m2. Average density for much watery rice fields with a total length of 1200 meters transect were as follows: (1) juvenile density was 0.89 individuals/m2, (2) pre-adult density was 0.08 individuals/m2, (3) adult density was 0.01 individuals/m2.Key words: population density, Fejervarya cancrivora, paddy field, Karawang District